2016
DOI: 10.1007/s13197-016-2446-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability, thermal stability and acceptability of coconut oil flavored with essential oils from black pepper and ginger

Abstract: The present study investigates the oxidative and thermal stability of flavoured oils developed by incorporating essential oils from black pepper and ginger to coconut oil (CNO) at concentrations of 0.1 and 1.0% (CNO P-0.1 , CNO P-1 , CNO G-0.1 , CNO G-1 ). The stability of oils were assessed in terms of free fatty acids, peroxide, panisidine, conjugated diene and triene values and compared with CNO without any additives and a positive control with synthetic antioxidant TBHQ (CNO T ). It was found that the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 21 publications
8
35
0
2
Order By: Relevance
“…Besides heating also produce many decomposed products that are also dark in color. Similar findings have been reported in color change of oils subjected to heating due to the accumulation of non-volatile decomposed products such as oxidized triacylglycerol and FFA that can lead to color changes which indicate the oil deterioration (Chandran et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Besides heating also produce many decomposed products that are also dark in color. Similar findings have been reported in color change of oils subjected to heating due to the accumulation of non-volatile decomposed products such as oxidized triacylglycerol and FFA that can lead to color changes which indicate the oil deterioration (Chandran et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the hempseed oil reached this value on the 6 th day, whereas the soybean oil reached this value on the 8 th day of storage upon heating for 4 hr at 180 °C. Other studies based on the measured PV have reported that the hydroperoxide content of these oils was very dependent on reaction conditions (Chandran, Nayana, Roshini, & Nisha, ; Frankel, ; Tańska, Mikołajczak, & Konopka, ). Also, it has been found that the peroxide content present after high‐temperature heating is descriptive of the thermal stability of the specific oils (Crnjar, Witchwoot, & Nawar, ).…”
Section: Resultsmentioning
confidence: 94%
“…α‐curcumene initially existed highest in relative amount (29.28 μg/100 g) but was not detected throughout the roasting. α‐curcumene is an aromatic monoterpenoid having an herbal odor, which can be found in foods such as pepper, rosemary, and wild carrot as well as medicinal herbs (Chandran, Nayana, Roshini, & Nisha, 2017). Tetradecane and tridecane were also found in high relative amounts at 0 min, 23.74 μg/100 g and 20.96 μg/100 g, respectively, and substantially decreased to 0.76 μg/100 g and 0.34 μg/100 g at 5 min.…”
Section: Resultsmentioning
confidence: 99%